Development of Matrix Tablets by Extrusion/ Spheronization Process Using Laboratory Extruder - R. K. Mohamed Mutahar; Nagaraja Sreeharsha; Aqsa Farheen; Sanjay Kumar Gupta; Azmath Fatima (Novel Aspects on Pharmaceutical Research Vol. 2, 2023)
The primary goal of this study is to formulate and evaluate matrix tablets (MTs) of Nicotinic acid by extrusion/Spheronization process using extruder. Wherein, a detailed examination of the influence of the process factors has also been concentrated. Extrusion is a process of converting raw material into a product of uniform shape and density by forcing it through a die under controlled conditions. Extruded MTs were initially made directly from the extruder rod die and then again by compressing the extruded granules using mixed polymers during spheronization. These MTs were then compared to those made by compressing powders directly. These extruded MTs had a longer release pattern and were found to have superior physical qualities, features of drug solubility, and uniformity of drug content. As all formulations best fit into first order release kinetics and Higuchi’s equation, the in vitro drug release data supports the diffusion-controlled nature of the release mechanism. The data were fitted into the Korsmeyer-Peppas model, which exposed abnormal transport kinetics, to confirm the results of the diffusion mechanism. The release rate result t20%, t50%, and t80%, of formulations tend to show similar to market product (MP) release rate. According to the model independent pair-wise approach 1 and 2 analysis, the MP profile and the dissolution profile of formulations can be superimposed. It was evident from the accelerated stability analyses of the improved formulations GEM.2 and TEM.2 that very little of the medication content deteriorated. At the end of six months, the release pattern was essentially unaltered and could be regarded as stable. Therefore, it can be said that extrusion/ Spheronization has higher potential as a process for creating MTs.